The PBL Model in Statistics to Improve Eighth-Grade Students’ Mathematical Problem-Solving Skills - Sandrawati Djafar; Sumarno Ismail; Kartin Usman (Faculty of Teacher Training and Education, 2026)
This study aims to improve students’ mathematical problem-solving skills through the implementation of the Problem-Based Learning model in Statistics material. The research was conducted in class VIII-1 at SMP Negeri 2 Tibawa with 26 students. This study uses classroom action research. The data collection techniques used were observation and tests. The instruments in this study consisted of teacher activity observation sheets, student activity observation sheets, and written tests. The study was conducted in two cycles. The implementation of learning by applying the Problem-Based Learning model to Statistics material in class VIII at SMP Negeri 2 Tibawa improved mathematical problem-solving skills. This is indicated by the results showing that mathematical problem-solving skills increased from 34.62% in cycle I to 88.46% in cycle II.